L’obligation générale de protéger le milieu marin contre la pollution En cadre d’UNCLOS 1982 - BELOUT, Samah (Journal of Human Sciences, 2020)
The international community members have contributed in establishing the maritime environment protection rules within the set of the law of sea rules, which was drafted in Montego Bay convention on the law of the sea 1982. These rules was set to reduce the pollution dangers in order to offer a total protection for the environment, characterized by the principle of the general commitment to marine environment protection. Based on this principle, the different legal rules aiming to protect the maritime environment from pollution started to emerge and divaricated; thus, there appeared new legal effects resulting from this general commitment concerning the definition of the states specialities, between the flag states, coastal states and port states. Moreover, new rules was set based on the international cooperation and solidarity in order to enable the states to face the maritime pollution that threatens their costs, in fact, it does threaten the overall maritime environment.